Video summarisation techniques on user-generated videos and character-oriented TV series - Lei, Zhuo (2020)
Video summarisation techniques is able to convey significant contents to represent the original video, which is sampling the frames to reduce the video length. Traditional related researches focus on edited videos, but exponentially increasing user-generated videos makes traditional methods ineffective, since they are often edited and only contain one shot. Moreover, it is difficult to achieve some universal criteria to generate summaries, even one single user may give different definitions for the same video. Thus, user-generated video summarisation is a subjective task. In the recent years, some researchers summarise videos by concentrating on some specified persons or objects. Hence, TV episodes are chosen, which is a strong platform consisting of various and vast information, as the experimental material to find all the occurrences of some specified characters.